Investigating EFL Students’ Perception of English Vocabulary Acquisition Through Online Gaming - Lusy Angraeni; Chuzaimah Chuzaimah; Fadli Nasir (Universitas Negeri Makassar, 2019)
This study focuses on university students’ opinion about secondary vocabulary acquisition through an online game. This study employs a descriptive quantitative method using questionnaire to gather the data. The whole population in this study was the fourth semester students of Akadami Bahasa Asing UMI. The samples were students who frequently play online game specifically Player Unknown’s Battleground (pubg), from class C1 until C4. The sample was taken by using purposive sampling technique. This research was conducted by distributing questionnaires to students who were respondents, after which they were input and analyzed through the SPSS program. The findings revealed that based on the 12 items that were given, the most chosen by students was item 2 and 8, students who understood the meaning of new vocabularies when playing games and students who made a new vocabulary list and wrote the translation in Indonesian were the opinions most chosen by students with an occasional scale of 60%.